The Macrophage Response to Mycobacterium tuberculosis and Opportunities for Autophagy Inducing Nanomedicines for Tuberculosis Therapy - Maphasa, Retsepile E.; Meyer, Mervin; Dube, Admire (Frontiers in Cellular and Infection Microbiology, 2021)
The major causative agent of tuberculosis (TB), i.e., Mycobacterium tuberculosis (Mtb), has developed mechanisms to evade host defense responses and persist within host cells for prolonged periods of time. Mtb is also increasingly resistant to existing anti-TB drugs. There is therefore an urgent need to develop new therapeutics for TB and host directed therapies (HDTs) hold potential as effective therapeutics for TB. There is growing interest in the induction of autophagy in Mtb host cells using autophagy inducing compounds (AICs). Nanoparticles (NPs) can enhance the effect of AICs, thus improving stability, enabling cell targeting and providing opportunities for multimodal therapy. In this review, we focus on the macrophage responses to Mtb infection, in particular, the mechanistic aspects of autophagy and the evasion of autophagy by intracellular Mtb. Due to the overlap between the onset of autophagy and apoptosis; we also focus on the relationship between apoptosis and autophagy. We will also review known AICs in the context of Mtb infection. Finally, we discuss the applications of NPs in inducing autophagy with the intention of sharing insights to encourage further research and development of nanomedicine HDTs for TB therapy.